Urine-derived stem cells in neurological diseases: current state-of-the-art and future directions - Cavaleiro, Carla; Afonso, Gonçalo J. M.; Oliveira, Paulo J.; Valero, Jorge; Mota, Sandra I.; Ferreiro, Elisabete (Frontiers in Molecular Neuroscience, 2023)
Stem cells have potential applications in the field of neurological diseases, as they allow for the development of new biological models. These models can improve our understanding of the underlying pathologies and facilitate the screening of new therapeutics in the context of precision medicine. Stem cells have also been applied in clinical tests to repair tissues and improve functional recovery. Nevertheless, although promising, commonly used stem cells display some limitations that curb the scope of their applications, such as the difficulty of obtention. In that regard, urine-derived cells can be reprogrammed into induced pluripotent stem cells (iPSCs). However, their obtaining can be challenging due to the low yield and complexity of the multi-phased and typically expensive differentiation protocols. As an alternative, urine-derived stem cells (UDSCs), included within the population of urine-derived cells, present a mesenchymal-like phenotype and have shown promising properties for similar purposes. Importantly, UDSCs have been differentiated into neuronal-like cells, auspicious for disease modeling, while overcoming some of the shortcomings presented by other stem cells for these purposes. Thus, this review assesses the current state and future perspectives regarding the potential of UDSCs in the ambit of neurological diseases, both for disease modeling and therapeutic applications.